Revealing Gender Disparities in Urban Green Space Utilization Using Mobile Phone Data - Xiankai Huang; Qijun Yang; Dandan Gu; Xiaoyuan Zhang; Jiahong Wang; Yaomin Zheng; Xun Zhang; Yongheng Feng; Jinlian Shi; Hongbo Yang (Ecosystem Health and Sustainability)
Urban green spaces (UGSs), such as parks and gardens, are vital for the health and well-being of city residents. However, unequal access to and utilization of UGS can impede social cohesion and sustainable development of cities. While many studies have investigated inequalities in accessibility to UGSs across various demographic groups, gender inequality in actual utilization of UGSs has received little attention largely due to the lack of data to reliably track UGS utilization by urban residents. Here, we leveraged the capacity of mobile phone data to track the movement of a large population and assessed the gender disparities in the utilization of UGSs among more than 77,000 residents residing in 2 populous communities in Beijing. We found that men spent 11% more time in UGSs and visited them 6% more frequently than women. This gender disparity varied across different socioeconomic groups. The middle-aged group exhibited an up to 46.4% greater disparity than other age groups, while the higher-income group showed a 12.4% larger disparity than the lower-income group. Additionally, the resident group with normal commuting distances had a 52.8% higher gender disparity, and the resident group with regular working hours had a 110% greater disparity compared to their respective counterpart groups. These findings contributed to environmental justice research by revealing the complex gender disparity in UGS utilization. The approach developed in the study provides an efficient way for identifying disparities in the utilization of UGS and designing effective strategies accordingly to alleviate inequalities in our study area and beyond.